RUMAH PASCAKOLONIAL DALAM BELOVED KARYA TONI MORRISON - Niko Fediyanto (Jurnal Lingua Idea, 2015)
The main problem in this research is the study of postcolonial as a phenomenon that exsistin the United States in a contemporary literary work, Beloved. Author presents spaces as a form of resistance. To solve the problem in this study used the perspective of space postcolonialism. This study uses the theory of space pascakonlonial to see criticism and symbols traumatic factors. The first thing that is done with this theory is seen forms of space depicted in the novel and saw the relationship between space with other elements, such as characters. Furthermore, researchers found a relationship and place it against the function of historical fact. The author makes some dominant place in this novel, which are the real world, the phenomenal world, and the house 124. There are things that are identical between the description of the existing space in the novel and the outside (history).